2019
DOI: 10.32098/mltj.04.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Treatment for Gonarthrosis Based on the Sequential Intra-Articular Injection of Linear and Cross-Linked Hyaluronic Acids

Abstract: Background. This study evaluates the clinical and biochemical effects of sequential intra-articular (IA) injections of linear (LHA) and cross-linked hyaluronic acid (CLHA) in patients with Gonarthrosis (GA). Methods. Thirty-nine (39) patients (age 64.89 ± 8.83) received first the LHA injection (0.8-1.2 MDa, 32mg/2ml) and after 1 week the CLHA (1.0 MDa and 2.0 MDa, 75mg/3ml) one; this round was repeated after 6 months. Clinical assessments-i.e. ultrasonography, visual analogic scale (VAS) for pain, range of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Our data are in agreement with the finding of Wu et al [ 24 ], who showed that high-molecular-weight HA attenuated tendinopathy by down regulating MMP-1 and -3 expression via CD44. Indeed, HA, beyond its physical and lubricating properties, is actively involved in regulating inflammatory responses mediated through the interactions with different substrates and receptors, among which CD44 represents a primary target [ 32 ] and has HA also effectively mitigated chondropathy and tendinopathy in clinical practice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data are in agreement with the finding of Wu et al [ 24 ], who showed that high-molecular-weight HA attenuated tendinopathy by down regulating MMP-1 and -3 expression via CD44. Indeed, HA, beyond its physical and lubricating properties, is actively involved in regulating inflammatory responses mediated through the interactions with different substrates and receptors, among which CD44 represents a primary target [ 32 ] and has HA also effectively mitigated chondropathy and tendinopathy in clinical practice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HA utilized in this pilot study is a blend of different MW linear-HA similar in composition to that exhibiting a strong and prompt anti-inflammatory activity in a previous study on osteoarthrosis (OA) from a previous study of our group [ 33 ]. Although completely different from each other, a common trait linking the two pathologies is the need to reduce the inflammatory process and its consequences, an effect that both the blends of HA proved to afford.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference between the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the KOOS is the inclusion of two additional domains, a five-item sport and recreation function domain, and a four-item QOL domain. Also, the pain domain and stiffness domain were changed to a seven-item symptom domain with more detailed questions (29). For each domain, scores were normalized on a "0-100" scale; zero for the worst result and 100 for the best result.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…Previous in vitro studies have shown that HA exerts an inhibitory effect on several MMPs (12,13) and HA treatment has been recently shown to reduce MMP-2 levels in SF of patients affected by knee OA (14). However, the effects of HA preparations may differ depending on method of production, treatment schedule, molecular weight, half-life within the joint, rheological properties and pharmacodynamics (15). Hymovis ® , a CE-marked and FDA-approved viscosupplementation preparation for intra-articular injection in OA patients is a gel made of linear HA partially chemically modified with an alkyl chain.…”
Section: Introductionmentioning
confidence: 99%